Fine tuning of Notch signaling by differential co-repressor recruitment during eye development of Drosophila. - Nagel, A.C.; Preiss, A. (Hereditas, 2011)
Notch signaling is fundamental to the regulation of cellular differentiation, cell growth and cell death in mammals as well as in invertebrates like Drosophila. Upon activation, the Notch receptor is cleaved and the intracellular part ICN assembles an activator complex around Suppressor of Hairless [Su(H)] that activates Notch target genes. Hairless (H) is the major antagonist of the Notch signaling pathway in Drosophila. In the absence of Notch signal, H binds to Su(H) and recruits two general co-repressors, Groucho (Gro) and C-terminal Binding Protein (CtBP); this repression complex downregulates Notch target genes. Previously we have shown that Gro and CtBP are recruited simultaneously to H and that they act in concert during wing and embryonic development. However, Gro and CtBP are utilized context-dependently by other transcription factors. Hence differential co-repressor recruitment by the Su(H)-H repressor complex is likewise conceivable. Here, we investigated the requirement for the co-repressors Gro and CtBP in H mediated Notch repression during several phases of eye development. Whereas both co-repressors appear likewise important during the specification of photoreceptor cells, we find differential requirement for the regulation of proliferation and cell death, respectively. During the early proliferative phase, H preferentially recruits Gro to inhibit Notch mediated growth of the eye disc. Elimination of superfluous interommatidial pigment cells, which depends on a late Notch signal, is antagonized by H and predominantly CtBP. In summary, differential recruitment of the co-repressors Gro and CtBP by H in a context-dependent manner ensures fine tuning of Notch signaling activity during eye development.